2002
DOI: 10.1046/j.1462-2920.2002.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and activity of Archaea in aerated activated sludge wastewater treatment plants

Abstract: The occurrence, distribution and activity of archaeal populations within two aerated, activated sludge wastewater treatment systems, one treating domestic waste and the second treating mixed domestic and industrial wastewater, were investigated by denaturing gradient gel electrophoresis (DGGE) analysis of polymerase chain reaction (PCR)-amplified ribosomal RNA gene fragments and process measurements. In the plant receiving mixed industrial and domestic waste the archaeal populations found in the mixed liquor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
47
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 35 publications
6
47
0
2
Order By: Relevance
“…However, large numbers of methanogenic organisms have been found in various activated sludge treatment plants [68,69]. Specifically, the same methanogenic orders (methanomicrobiales and methanobacterales) found in the present work have been found in low dissolved oxygen level (0.5 -0.8 mg/l) activated sludge processes by other authors [22].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…However, large numbers of methanogenic organisms have been found in various activated sludge treatment plants [68,69]. Specifically, the same methanogenic orders (methanomicrobiales and methanobacterales) found in the present work have been found in low dissolved oxygen level (0.5 -0.8 mg/l) activated sludge processes by other authors [22].…”
Section: Discussionsupporting
confidence: 86%
“…However, large numbers of methanogenic organisms have been found in various activated sludge treatment plants [68,69]. Specifically, the same methanogenic orders (methanomicrobiales and methanobacterales) found in the present work have been found in low dissolved oxygen level (0.5 -0.8 mg/l) activated sludge processes by other authors [22].However, the methanogenic archaea found in the samples was probably due, as mentioned above, to sludge from the anaerobic digester being pumped back into the primary clarifier. It has been reported that methanogens in aerated sludges may simply be able to survive high oxygen levels but are inactive until reducing conditions are established [22].…”
supporting
confidence: 86%
See 3 more Smart Citations